2013
DOI: 10.1371/journal.pone.0053657
|View full text |Cite
|
Sign up to set email alerts
|

Human Granuloma In Vitro Model, for TB Dormancy and Resuscitation

Abstract: Tuberculosis (TB) is responsible for death of nearly two million people in the world annually. Upon infection, Mycobacterium tuberculosis (Mtb) causes formation of granuloma where the pathogen goes into dormant state and can live for decades before resuscitation to develop active disease when the immune system of the host is weakened and/or suppressed. In an attempt to better understand host-pathogen interactions, several groups have been developing in vitro models of human tuberculosis granuloma. However, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
218
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(229 citation statements)
references
References 63 publications
6
218
2
Order By: Relevance
“…Consistent with this observation, Mycobacterium bovis BCG strains that are inhibited in their ability to mediate TAG hydrolysis are attenuated for survival in vitro during and following resuscitation from NRP (60,61). Similarly, an M. tuberculosis mutant deleted in triacylglycerol-1 synthase (⌬tgs1), an enzyme used to make TAGs, is compromised in its ability to accumulate intracellular TAGs and is unable to enter into NRP in an in vitro human TB granuloma model (73). Finally, an M. tuberculosis mutant deleted in lipase lipY, which is required for TAG hydrolysis, is compromised in its ability to mobilize stored TAGs and is unable to reactivate from NRP in the granuloma model system (73).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Consistent with this observation, Mycobacterium bovis BCG strains that are inhibited in their ability to mediate TAG hydrolysis are attenuated for survival in vitro during and following resuscitation from NRP (60,61). Similarly, an M. tuberculosis mutant deleted in triacylglycerol-1 synthase (⌬tgs1), an enzyme used to make TAGs, is compromised in its ability to accumulate intracellular TAGs and is unable to enter into NRP in an in vitro human TB granuloma model (73). Finally, an M. tuberculosis mutant deleted in lipase lipY, which is required for TAG hydrolysis, is compromised in its ability to mobilize stored TAGs and is unable to reactivate from NRP in the granuloma model system (73).…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, an M. tuberculosis mutant deleted in triacylglycerol-1 synthase (⌬tgs1), an enzyme used to make TAGs, is compromised in its ability to accumulate intracellular TAGs and is unable to enter into NRP in an in vitro human TB granuloma model (73). Finally, an M. tuberculosis mutant deleted in lipase lipY, which is required for TAG hydrolysis, is compromised in its ability to mobilize stored TAGs and is unable to reactivate from NRP in the granuloma model system (73). Thus, LDs represent an important energy reservoir utilized by M. tuberculosis for survival during and resuscitation from NRP.…”
Section: Discussionmentioning
confidence: 99%
“…Single cell cultures of human macrophages or other peripheral blood cells have often been used 6,7 . The disadvantage of this approach is that they cannot reflect the dynamics of different cell types operating together in a lung tissue exposed to M. tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…A positive chest X-ray for healed or active pulmonary tuberculosis, contact history, elevated erythrocyte sedimentation rate (ESR), positive tuberculin test and sampling by laparoscopy may specify the need for further investigations [19,20,21]. Studies such as serial sections of tissues need to be studied, because the lesions are frequently erratic and that a positive endometrial culture for TB, is found only in about 25% of cases of tuberculous endometritis as the endometrium is often focal and the functionalis layer is shed every four weeks (granulomas take two weeks to develop) [22,23]. Moreover, due to the cyclical shedding of the endometrium, granulomas do not have enough time to form, so the granulomatous endometrium may not show evidence of tuberculosis in all the cycles.…”
Section: Introductionmentioning
confidence: 99%